Some Geometric Results for a New subfamily of Regular Functions in the Generalized Janowski Domain (European Journal of Pure and Applied Mathematics, 2025)
Let $\mathcal{SK}\left[ P,Q;\alpha ,\beta \right] $ denote the subfamily of normalized regular functions $g(\xi )=\xi +d_{2}\xi ^{2}+d_{3}\xi ^{3}+d_{4}\xi ^{4}+...$ in the open unit disk $ \Delta $ holding the next subordination condition:\begin{equation*}\frac{\alpha g\left( \xi \right) +\beta \xi g^{\prime }\left( \xi \right) }{%\alpha \xi +\beta g\left( \xi \right) }\prec \frac{1+\left[ Q+\left(1-\gamma \right) \left( P-Q\right) \right] \xi }{1+M\xi },\end{equation*}where $0\leq \alpha ,\beta \leq 1$, $-1\leq Q
Keywords: regular function; starlike